EMBROIDERY OF BUKHARA OF THE XIX CENTURIES EARLY - XX CENTURIES - Доцент Мухайе Баратовна Азимова (Web of Journals Publishing, 2025)
The art of embroidery has an ancient history. Almost all countries of the East are considered its homeland. But the wall paintings of the cities of Varakhsha and Paykent, dating back to the VI-VIII centuries, with patterned clothes of people and veils on horses and elephants, indicate that embroidery was developed in the early Middle Ages.
Keywords: Art, embroidery, history, samples, ancient, products, painting, clothing